2014
DOI: 10.1080/21642583.2014.999389
|View full text |Cite
|
Sign up to set email alerts
|

A survey on retail sales forecasting and prediction in fashion markets

Abstract: Sales forecasting is an essential task in retailing. In particular, consumer-oriented markets such as fashion and electronics face uncertain demands, short life cycles and a lack of historical sales data which strengthen the challenges of producing accurate forecasts. This survey paper presents state-of-the-art methods in the sales forecasting research with a focus on fashion and new product forecasting. This study also reviews different strategies to the predictive value of user-generated content and search q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Likewise—in an industry like retail—ML can play a strategic role in sales forecasting (Beheshti-Kashi et al 2015; Kaneko and Yada 2016), new store placement (Karamshuk et al 2013), and in fraud detection (Trinh et al 2011). In the latter, ML is used in collecting data like in the process described by Dietterich in the environmental sensor example, by converting signals into data.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise—in an industry like retail—ML can play a strategic role in sales forecasting (Beheshti-Kashi et al 2015; Kaneko and Yada 2016), new store placement (Karamshuk et al 2013), and in fraud detection (Trinh et al 2011). In the latter, ML is used in collecting data like in the process described by Dietterich in the environmental sensor example, by converting signals into data.…”
Section: Discussionmentioning
confidence: 99%
“…They developed a two-stage sales forecasting system and showed the real benefits of advanced forecasting techniques for fast fashion retailing. For an overview of sales forecasting literature related to retail and fashion sales forecasting under conditions of lack of historical data, see Beheshti-Kashi et al (2015). For a recent comprehensive review of computational models that can be applied for fast fashion demand forecasting, see Ren et al (2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several researchers who have to discuss sales forecasting and its application to real-life problems. Samaneh et al [12] did a survey on retail sales forecasting and forecasting in fashion markets. They concluded that conventional forecasting methods face challenges in producing accurate sales data for new products and consumer-oriented goods.…”
Section: Related Workmentioning
confidence: 99%